Virtual environments in architecture and planning design: 4 possible approaches - Mohamed Eshaq, Ahmad Rafi; Karboulonis, P.; Fazidin, J.; Badrolhisham, H. (University of Sydney, 2003)
Advancements in information retrieval (IR), local and wide area networks (LAN, WAN) and the Internet, human-computer interaction (HCI), and virtual reality (VR) technologies have enabled the emergence and availability of affordable real-time computer data visualisation and manipulation systems that can be deployed and interfaced to most Computer Aided Design (CAD) software systems. However, the rapid advancement and adoption of information visualisation in different areas is currently challenging VR system designers to formulate and deploy strategies and tools to effectively visualise, navigate and effectively communicate various types of information within a virtual environment (VE). A further problem relates to the fact that even within a single area or application the requirements are still diverse to the extent that different approaches and technologies still need to be employed before a satisfactory solution is reached. This paper presents four possible approaches in identifying and designing effective VR systems for architecture and planning design to allow the user to effectively communicate and share their experiences and ideas in a collaborative manner. It is also proposed that VEs should look beyond plain representations and reproductions of the real world environments that they portray and bear higher interpretation and expression values. The value of eliciting structuring and interfacing information and knowledge to a VE is also highlighted, as is the need for efficient database systems and CAD systems capable of exchanging information and data with VEs. Current efforts in prolonging the lifetime of VEs are being examined through four case studies that highlight the ever-escalating requirements that currently face VR researchers.